Analysis of Budget Disbursement Budget in The End of 2018 in Bangka Belitung Island Province - Hendarti Tri SM (Future Science, 2021)
According to Permendagri No. 13 Year 2006 on the principles of general management of the financial area is the financial area which is managed in an orderly, obedient to the regulatory legislation, effective , efficient , economical, transparent and accountable to pay attention to the principles of fairness, appropriateness and usefulness to society . Regional financial management includes planning, determination, implementation, accountability , as well as guidance and supervision of the management of the regional budget. Due to the buildup of this budget disbursement, the Provincial Government of Bangka Belitung Islands is deemed necessary to conduct an evaluation related to the distribution of the budget. One of the factors causing the budget absorption cannot reach 100% is the auction process, which certainly involves rules and regulations. Another factor that causes low budget absorption is the inability of HR to manage tasks. From the results of the research that has been done, it can be seen that the accumulation of budget disbursement at the end of 2018 has many negative impacts. One of them is the decline in the Bangka Belitung Islands Province Budget Implementation List (DIPA) for 2019 by 363.3 billion. The decline in DIPA occurred due to the lack of maximum Bangka Belitung Islands Provincial Government in maximizing DIPA revenue the previous year. This indicates the lack of good planning that has been made by the government resulting in budgetary congestion at the end of the year. One strategy to anticipate the low budget absorption is by maximizing the implementation of activities and not piling up activities at the end of the year. Key words: Stacking of budget disbursement, APBN, withdrawal of funds at the end of the year.